Selective suppressive effects of Trypanosoma cruzi on activated human lymphocytes. - Beltz, L A (1989)
The acute phase of Chagas' disease is accompanied by immunosuppression. To explore the underlying mechanism(s), we used an in vitro culture system in which the capacities of activated human peripheral blood mononuclear cells to express interleukin-2 receptors (IL-2R) and proliferate are markedly inhibited in the presence of Trypanosoma cruzi, the etiologic agent. The present work was designed to define the earliest time at which T. cruzi-induced suppression is manifested in terms of IL-2R expression on the cell surface and establish whether expression of other lymphocyte activation markers is also suppressed by the parasite. We found that expression of IL-2R by human peripheral blood mononuclear cells cocultured with T. cruzi and stimulated with either phytohemagglutinin or anti-CD3 (a monoclonal antibody specific for an epitope of the T cell receptor complex T3-Ti) was significantly suppressed as early as 12 h after culture initiation. Both the percentage of IL-2R+ cells and the surface density of IL-2R, measured by flow cytometry, were affected. However, expression of EA1, a human lymphocyte activation antigen known to be expressed 4 to 6 h after stimulation, was not altered by T. cruzi whether phytohemagglutinin or anti-CD3 was used. On the other hand, expression of transferrin receptors (TfR), which first occurs between 20 and 24 h after lymphocyte activation, was markedly suppressed by T. cruzi. This effect was denoted by significant reductions in both the percentage of TfR+ cells and the cell surface density of TfR whether phytohemagglutinin or anti-CD3 was used as the mitogen and was observed at all test times, i.e., at 24, 48, 72, and 96 h. Because expression of IL-2R and TfR is required for lymphoproliferation but that of the EA1 lymphocyte activation marker is apparently not, these results are consistent with the possibility that T. cruzi, at a relatively early stage during lymphocyte activation, selectively affects certain key events on which clonal expansion is dependent. Inhibition of IL-2R and TfR expression by the parasite might play a role in causing the suppressive effects associated with acute Chagas' disease.